Non-Excitatory Amino Acids, Melatonin, and Free Radicals: Examining the Role in Stroke and Aging - Victoria Jiménez Carretero; Eva Ramos; Pedro Segura-Chama; Adan Hernández; Andrés M Baraibar; Iris Álvarez-Merz; Francisco López Muñoz; Javier Egea; José M. Solís; Alejandro Romero; Jesús M. Hernández-Guijo (MDPI AG, 2023)
The aim of this review is to explore the relationship between melatonin, free radicals, and non-excitatory amino acids, and their role in stroke and aging. Melatonin has garnered significant attention in recent years due to its diverse physiological functions and potential therapeutic benefits by reducing oxidative stress, inflammation, and apoptosis. Melatonin has been found to mitigate ischemic brain damage caused by stroke. By scavenging free radicals and reducing oxidative damage, melatonin may help slow down the aging process and protect against age-related cognitive decline. Additionally, non-excitatory amino acids have been shown to possess neuroprotective properties, including antioxidant and anti-inflammatory in stroke and aging-related conditions. They can attenuate oxidative stress, modulate calcium homeostasis, and inhibit apoptosis, thereby safeguarding neurons against damage induced by stroke and aging processes. The intracellular accumulation of certain non-excitatory amino acids could promote harmful effects during hypoxia-ischemia episodes and thus, the blockade of the amino acid transporters involved in the process could be an alternative therapeutic strategy to reduce ischemic damage. On the other hand, the accumulation of free radicals, specifically mitochondrial reactive oxygen and nitrogen species, accelerates cellular senescence and contributes to age-related decline. Recent research suggests a complex interplay between melatonin, free radicals, and non-excitatory amino acids in stroke and aging. The neuroprotective actions of melatonin and non-excitatory amino acids converge on multiple pathways, including the regulation of calcium homeostasis, modulation of apoptosis, and reduction of inflammation. These mechanisms collectively contribute to the preservation of neuronal integrity and functions, making them promising targets for therapeutic interventions in stroke and age-related disorders.